Phenotypic stability of reproductive traits in dorper sheep under intensive tropical production systems - Rismasari Rismasari; Dwi Wijayanti; Ulul Azmi; Dian Andriansyah; Mutasem Abuzahra (Universitas Airlangga, 2026)
This study evaluated the reproductive performance of Dorper sheep in an intensive system in West Java, Indonesia. Data included ewe parity (P1 and P2), lambing interval (LI), litter size at birth (LSB), weaning litter size (WLS), age at first lambing (AFL), annual reproductive rate (ARR), and offspring sex ratio. Data analysis was performed using the Kruskal–Wallis and Mann–Whitney tests. The strength of the correlation was interpreted based on the correlation coefficient (r), where values ​​close to 0 indicate a weak relationship, while values ​​close to ±1 indicate a strong relationship. Statistical significance was set at P < 0.05. The results showed a stable ARR value of 1.64 across genders, confirming the success of the accelerated lambing system (3 lambing in 2 years) with an average lambing interval of 259–265 days. There was an increase in the number of male lambs, reaching 60% by 2025, which correlated with the improved pre-conception nutritional status of the ewe. Parity did not affect the number of offspring per litter but demonstrated good stability in the trophic environment. Spearman’s correlation analysis showed that the relationships between reproductive parameters tended to be weak and insignificant, indicating that reproductive traits were relatively independent. In conclusion, an intensive rearing system can overcome tropical climate challenges and maximize the genetic potential of Dorper sheep. An ARR of 1.64 indicates good reproductive performance under the evaluated production conditions. Although a higher proportion of male offspring may be advantageous in meat-oriented production systems, further studies evaluating both the biological determinants of offspring sex ratio and its economic impact are needed before management recommendations can be made.